Birth Defects Data from Surveillance Hospitals in Hubei Province, China, 200l - 2008 - Lh Tu; H Li; Hp Zhang; Xd Li; Jj Lin; Cl Xiong (Tehran University of Medical Sciences, 2012)
Background: To determine the prevalence and characteristics of birth defects in perinatal infants in Hubei Province during 200l-2008. Methods: The prevalence of birth defects in perinatal infants delivered after 28 weeks or more was analyzed in Hubei surveillance hospitals during 200l-2008. Results: The incidence of birth defects in perinatal infants from 200l to 2008 was 120.0 per 10,000 births, and was increased by about 41% from 81. 1 in 2001 to 138.5 per 10,000 births in 2008. The incidence in the first 4 years (2005-2008) was much higher than the latter four (2001-2004) (χ2=77.64 , P <0.05). The difference in prevalence between urban and rural was of no significance in 2008 (χ2=0.03，P >0.05), but that between male and female was significant (χ2=5.24 , P <0.05), as the former prevalence was much higher. The prevalence of birth defects was slightly higher among mothers over 35 years old than those under 35 years old, but with no significance (χ2=1.98, P >0.05). The two leading birth defects were cleft lip and/or palate and polydactyly, followed by congenital heart disease, hydrocephaly, external ear malformation and neural tube defects. The prevalence of congenital heart disease was rising. Conclusions: Eight years' birth defects data indicate that the birth defect rate was on the rise and the birth defects prevalence in Hubei province should be valued.